2017
DOI: 10.1177/0301006616689279
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Odour Intensity and Valence to Moral Decisions

Abstract: Meta-analytic evidence showed that the chemical senses affect moral decisions. However, how odours impact on morality is currently unclear. Through a set of three studies, we assess whether and how odour intensity biases moral choices (Study 1a), its psychophysiological responses (Study 1b), as well as the behavioural and psychophysiological effects of odour valence on moral choices (Study 2). Study 1a suggests that the presence of an odour plays a role in shaping moral choice. Study 1b reveals that of two iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 104 publications
4
20
0
Order By: Relevance
“…Detection threshold was determined using a two-alternative forced-choice ascending staircase paradigm with seven reversals and no feedback 36 . Each trial included one target (a bottle with the diluted odor) and one control stimulus (a bottle with the diluent only).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection threshold was determined using a two-alternative forced-choice ascending staircase paradigm with seven reversals and no feedback 36 . Each trial included one target (a bottle with the diluted odor) and one control stimulus (a bottle with the diluent only).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the olfactory system is anatomically connected to the limbic system through brain regions including the amygdala, piriform cortex, insula, orbitofrontal cortex and anterior cingulate cortex 30 , 32 , 33 . This preferred link is manifested in the noteworthy ability of odors to automatically induce mood changes 31 and to impact cognition and behavior 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this paradigm has also other advantages: it allowed studying the effects of the social odor when they are unconsciously perceived. As seen in a previous study 63 , odor effects can emerge irrespective of the perceiving the presence of an odor; moreover, masking the social odor limited the inter-individual differences in odor intensity and pleasantness that can significantly affect decisions, as it seemed in the previous cases when intensity and pleasantness differences across odor conditions were evident 17,63 . Here we succeeded in making these conditions perceptually similar for intensity, familiarity and pleasantness, removing the possible confounding effect of these factors on the differences in the moral decisions.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, Schnall et al 17 demonstrated that the presence of a disgusting odor toughens the judgment on vignettes without moral content. Also, we have previously shown that the subliminal exposure to a neutral (non-social) odor can bias moral choices towards options characterized by harm avoidance (deontological options 18 ). Generally speaking, a harm is justified (or to some extent forgiven) if it comes as the side-effect of a moral action carrying a greater benefit compared to an intentional harm with the same outcome 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation